The Abundance of Karst-Riparian Forest in the Catchment Area of Sampolawa River Baubau, Southeast Sulawesi - Erif, La Ode Muhammad/ L. O. M (Faculty of Biology Universitas Gadjah Mada, 2013)
Riparian forest is a source energy and matter for the aquatic ecosystem. The abilities of riparian forest are to control and recycle the allochthonous inputs from the upland drainage basin and the river itself. This processess are a fundamental aspect of river ecology. We studied the riparian forest at protected forest of Sampolawa headwater river, Baubau, Southeast Sulawesi. We focussed on the structure and composition of species richness of the forest. Data were collected using quadrate method, 20mx20m, with 4 replicates at each river side. Results reveal that the forest compossed of 7 growth-forms, trees, saplings, seedlings, palm, herbs, liana, and spike moss. The species richness of the was 35. The tree species of Sphatolobus sp., Aglaia silvestris, and Canarium asperum dominated the riparian forest. Similarly the sapling dominant were Sphatolobus sp., Aglaia sp., and Chrysophyllum lanceolatum, as well as the seedlings of Sphatolobus sp., Palaquium obovatum and Chrysophyllum lanceolatum. Thus the Sphatolobus sp. will be the future tree, and also all the tree species characterized the riparian forest of karst ecosystem of Sampolawa headwaters river. Soil nutrients of NO3, NH4, PO4, and C organic were high, which indicated that the litterfall decomposition occurred ath the forest riparian floor. The Riparian forest was a primary forest and very diversed in species richnes baut low density. Their present characterized the riparian forest at headwaters of Sampolawa River setting in the karst ecosystem.